A Comparative Study of Online and Physical Education in Pakistani Higher Education Institutions: Preferences, Effectiveness, and Challenges - Sain, Zohaib Hassan; Thelma, Chanda Chansa; Adiyono, Adiyono; Lawal, Uthman Shehu (Universitas Nurul Jadid Probolinggo, Indonesia, 2023)
Combining online and physical education transformed Pakistan's higher education. This study compares educational methods' pros and cons. This study investigates Pakistani higher education institutions' instructional modes' performance, student choice, and challenges. Good mixed-methods study used quantitative and qualitative data. This extensive survey comprised 500 Pakistani public and private college students. Students, instructors, and administrators were carefully questioned to confirm the results. Theme analysis examined qualitative data, whereas descriptive statistics, t-tests, and regression analysis examined quantitative data. According to data, many students choose online education for its flexibility and convenience. Student engagement and success are lower in online education than in physical education. Physical education is superior to high-quality education despite logistical restrictions due to active involvement and controlled learning conditions. Technology, the digital divide, accessibility, and packed classrooms affect online and physical education. The paper recommends separate online and physical education for Pakistani higher education students. A hybrid paradigm combining both modalities' capabilities is proposed. These results show policymakers and educators require technical infrastructure, digital literacy, and inclusive education. All Pakistani children need these programs for a fair and practical education.